2018
DOI: 10.3174/ajnr.a5815
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Leukocortical Lesions in Multiple Sclerosis and Their Association with Physical and Cognitive Impairment: A Comparison of Conventional and Synthetic Phase-Sensitive Inversion Recovery MRI

Abstract: BACKGROUND AND PURPOSE: Cortical lesions are common in multiple sclerosis and are included in the latest diagnostic criteria. The limited sensitivity of cortical MS lesions on conventional MR imaging can be improved by phase-sensitive inversion recovery. Synthetic MR imaging could provide phase-sensitive inversion recovery without additional scanning, but the use of synthetic phase-sensitive inversion recovery remains to be validated. We aimed to compare the ability and clinical value of detecting leukocortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…Recently, conventional and synthetic PSIR were compared for the detection of cortical lesions in patients with multiple sclerosis. 16 In that study, synthetic PSIR showed similar sensitivity to conventional PSIR. 16 We did not acquire conventional PSIR, so we could not compare its performance with that of synthetic PSIR in the infant brain.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Recently, conventional and synthetic PSIR were compared for the detection of cortical lesions in patients with multiple sclerosis. 16 In that study, synthetic PSIR showed similar sensitivity to conventional PSIR. 16 We did not acquire conventional PSIR, so we could not compare its performance with that of synthetic PSIR in the infant brain.…”
Section: Discussionmentioning
confidence: 67%
“…16 In that study, synthetic PSIR showed similar sensitivity to conventional PSIR. 16 We did not acquire conventional PSIR, so we could not compare its performance with that of synthetic PSIR in the infant brain. A prospective study on this subject is needed in the future.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Quantitative synthetic MR imaging is a time-efficient MR imaging technique that enables simultaneous quantification of T1 and T2 relaxation times and proton attenuation and allows the creation of any contrast-weighted image, including DIR and PSIR, without additional scanning time. [9][10][11][12][13] Previous studies have shown that synthetic MR imaging is useful for detecting and characterizing MS lesions. 10,11,14 However, these studies were based on a multisection 2D acquisition, providing a relatively low resolution in the section direction.…”
mentioning
confidence: 99%
“…Когнитивные функции, наряду с функцией поддержания равновесия и локомоций, а также контроля эмоционального статуса, задействуют большинство отделов переднего мозга и мозжечка [10], следовательно, они могут отражать степень эффективности внутримозговых соотношений. РС как демиелинизирующее заболевание, поражающее преимущественно белое вещество больших полушарий, комиссур и мозжечка, в существенной степени снижает возможности обеспечения интегративной активности мозга [11,12].…”
unclassified